An analysis of the library usage patterns of law students of the U.P. College of Law - Balidoy, Rosemarie D.; Aguirre, Vyva Victoria M. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
This research sought to determine the library usage patterns of students the University of the Philippines College of Law in relation to their personal attributes, legal research needs, and the library's facilities, resources and services.
The sampling technique used for this is the purposive sampling technique. Survey questionnaires were distributed to 183 respondents, of which 133 were returned. The data gathered from the survey were interpreted and analyzed using the SPSS. The hypotheses of the study were tested using the Pearson correlation and descriptive statistics such as frequency distributions, measures of central tendency such as the mean, median and mode.
This study found out that majority of the respondents use the law library almost everyday. Majority of the respondents are not satisfied with the current schedule of the library hours. Respondents viewed the help given by the librarian and library staff in answering reference queries as very good. Likewise, the librarian and the library staff are assessed by the respondents as helpful and effective. The law books collection, legal and other periodical collections were assessed by the users as adequate.
The study found that some of the personal attributes of the law students have a significant relationship with their library usage patterns. These were civil status, hour/s of employment, and use of other libraries/resources. The other personal attributes of age, gender, distance of residence from the U.P. Campus, year level and academic performance were found to be insignificant. Hence, the hypothesis that the users' personal attributes have an impact on the law students' utilization of the library, was partially accepted and the null hypothesis could not be fully rejected.
The variable current schedule of library hours under the library facilities, services and resources was the only variable that had a significant relationship with the library usage patterns of law students. Therefore, the hypothesis that the U.P. College of Law Library/s facilities, services and resources affect the users' legal research and library usage patterns can neither be rejected nor accepted.
The study found a significant relationship between the students' library usage patterns and the influence of the faculty members. The same positive result was found of the students' research needs. Therefore, the hypothesis that the faculty members of the UP College of Law influence the law students' legal research and library use patterns is accepted. The hypothesis that legal research needs influence the law students to use the library is likewise accepted.
Some recommendations for improvement of the library's resources, facilities and services are offered in this paper based on the comments and suggestions of the respondents and the researcher's observations.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines College of Law -- Students; University of the Philippines College of Law Library; Library use studies -- Philippines -- Quezon City